2004
DOI: 10.1158/1078-0432.ccr-03-0118
|View full text |Cite
|
Sign up to set email alerts
|

Very High Frequency of Hypermethylated Genes in Breast Cancer Metastasis to the Bone, Brain, and Lung

Abstract: Purpose: Most often it is not the primary tumor, but metastasis to distant organs that results in the death of breast cancer patients. To characterize molecular alterations in breast cancer metastasis, we investigated the frequency of hypermethylation of five genes (Cyclin D2, RAR-␤, Twist, RASSF1A, and HIN-1) in metastasis to four common sites: lymph node, bone, brain, and lung.Experimental Design: Methylation-specific PCR for the five genes was performed on DNA extracted from archival paraffin-embedded speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
3
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 16 publications
3
93
3
1
Order By: Relevance
“…The gene is methylated frequently in breast cancer [14,15,18] and even normal breast tissue [38], which may result in loss of expression and a loss of control of cellular proliferation. Unlike previous studies, in which there was found a positive association between RAR-β 2 hypermethylation and metastasis in breast tumor [15,18], we found no associations between hypermethylation of RAR-β 2 gene and metastasis and lymphovascular invasion. However, we found inverse associations between histological and nuclear grade and RAR-β 2 hypermethylation among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene is methylated frequently in breast cancer [14,15,18] and even normal breast tissue [38], which may result in loss of expression and a loss of control of cellular proliferation. Unlike previous studies, in which there was found a positive association between RAR-β 2 hypermethylation and metastasis in breast tumor [15,18], we found no associations between hypermethylation of RAR-β 2 gene and metastasis and lymphovascular invasion. However, we found inverse associations between histological and nuclear grade and RAR-β 2 hypermethylation among postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the association between gene hypermethylation and biological or clinical properties of breast tumors [13][14][15][16][17][18][19]. An association between CpG island hypermethylation of p16 and RAR-β 2 genes and poorly differentiated breast tumors was found in two previous studies [14,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 No significant differences in the expression levels of p53, Bcl-2, E-cadherin, matrix metalloproteinase-9, tissue inhibitor of metalloproteinase-1, epidermal growth factor (EGF) receptor, cyclooxygenase 2, or Bax were observed between the primary tumors and brain metastases. In contrast, Mehrotra and colleagues 49 identified a DNA hypermethylation phenotype in tissue blocks containing metastatic lesions of breast cancer, including eight brain metastatic lesions. Hypermethylation of cyclin D2, retinoic acid receptor-␤, and hin-1 occurred more frequently in brain metastases than in an unmatched cohort of primary breast carcinomas whereas hypermethylation of other genes, including twist and RassF1A, was not significantly different.…”
Section: Tissue-based Studiesmentioning
confidence: 87%
“…The mechanisms of cyclin d2 repression in breast tumors are poorly understood but are often correlated to a hypermethylation of its promoter region (23,45,46). The cyclin d2 gene is as well-frequently downregulated in various breast cancer cell lines and Cyclin D2 overexpression in mice mammary gland leads to inhibition of the Cyclin D1 oncogene phosphorylation and therefore activation (23,26,47).…”
Section: Discussionmentioning
confidence: 99%